Alevinagem de tambatinga (Colossoma macropomum x Piaractus brachypomus) suplementada com simbiótico em sistemas de bioflocos - Lira, Kárita Fernanda da Silva (2022)
The present study aimed to evaluate the effect of the biofloc system and dietary supplementation with symbiotic on zootechnical performance, intestinal histomorphometry of tambatinga fingerlings (Colossoma macropomum x Piaractus brachypomus) and on the mitigation of stress responses when fish are subjected to management carriage. A total of 288 tambatinga fingerlings (initial average weight 15,56 ± 0,19 g) were distributed in 16 polyethylene boxes (18 fish/box) with constant aeration, in a closed system, half of the boxes in a clear water system (AC) and the other half in biofloc system (BFT). During the experimental period, lasting 85 days, the fish were fed with commercial feed for omnivorous fish in the growth phase (40% crude protein), incorporated with symbiotic (DB Aqua®). At the end of this period, the fish were captured, placed in plastic bags with water and oxygen and transported for 3 hours. The experimental design was completely randomized (DIC) with 4 treatments: clear water + commercial feed (CA), clear water + commercial feed with symbiotic addition (CA+ Simb), biofloc system + commercial feed (BFT) and biofloc system + commercial feed with addition of symbiotic (BFT + Simb). Biometrics were performed fortnightly for weighing and gauging body measurements (Total Length - CT and standard - CP) and zootechnical performance indices were evaluated, such as final biomass (BF), average weight gain, biomass gain, average daily gain, daily feed intake (CR), survival rate (TS), body condition factor (FCC) and apparent feed conversion (CAA). At the end of the experiment, the fish were sacrificed and the intestines were collected to evaluate the length and relative weight and histomorphometry of the intestinal mucosa (villus height and width). Blood sampling occurred before transport (Base); after transport (Arrival) and 48h after this procedure to assess physiological indicators of stress, such as blood glucose, leukocyte respiratory activity, total erythrocyte count and levels of chloride, total protein, albumin and globulin. The use of the symbiotic in the diet of tambatinga fingerlings in clear water resulted in greater weight and length of the animals and there was a positive effect of bioflocs that allowed a greater development of intestinal villi. The physiological responses of tambatingas submitted to transport were similar between the treatments tested, so that the biofloc rearing system and dietary symbiotic supplementation were not able to minimize the effects of stress caused by this procedure.